Linking microscopic interactions with macroscopic effects. (May 2017) - Wood, Jennifer L.; Franks, Ashley E.; Egidi, Eleonora
Abstract: Understanding how biotic interactions impact plant community assembly is a long‐standing goal in ecology, but studies of biotic interactions in this context are often limited to macro‐interactions. In this issue of Journal of Vegetation Science, Sonkoly et al. synthesize current knowledge regarding the impact of cyanobacteria on terrestrial plants and show that cyanotoxins can alter germination and establishment success in grassland communities. Abstract : Research investigating biotic interactions that influence plant‐community assembly are often limited to macrointeractions. In this issue of Journal of Vegetation Science, Sonkoly et al. synthesize current knowledge regarding the impact of cyanobacteria, a microorganism, on terrestrial plants and demonstrate their impact on grassland‐community assembly. We discuss the importance and challenges of incorporating micro‐interactions into macro‐ecological processes.